High-resolution carbon and oxygen isotope records in the Chang 7 organic-rich shale of the Yanchang formation, Ordos Basin, China and their geological significance - Deng, Haowen (Frontiers in Earth Science, 2025)
The Late Triassic Chang 7 Member lacustrine organic-rich shale in the Ordos Basin is the most significant source rock for the Mesozoic oil system in the basin. This study utilizes high-resolution source rock samples to systematically analyze the organic carbon isotopes and carbonate carbon-oxygen isotopes of the Chang 7 Member source rocks. The results indicate that the average δ13Ccarb values for the Chang 71 to Chang 73 sub-members are 0.17‰, 0.33‰, and −2.8‰, respectively, and the average δ18Ocarb values are −14.1‰, −14.3‰, and −16.0‰, respectively. The Chang 73 sub-member exhibits anomalously low δ13Ccarb and δ18Ocarb values due to the influence of volcanic and hydrothermal activity. The carbon-oxygen isotopes, together with other element proxies, indicate that the Ordos Basin had semi-closed to semi-open hydrological conditions during the depositional periods of Chang 71 and Chang 72, with an overall warm and humid climate. The climate during the Chang 72 depositional period was relatively stable, while the Chang 71 period showed a trend towards increasing aridity. The lake during the Chang 7 depositional period had high paleo-productivity, with sedimentary organic matter being of mixed origin, primarily from aquatic organisms with some contribution from C3-type terrestrial higher plants. The findings of this study provide support and reference for research on paleoclimate, paleoenvironment, and organic matter enrichment mechanisms in the region.